A low‐profile antenna with circularly polarized reconfigurable and omnidirectional radiation patterns. Issue 1 (11th November 2020) - Yan, Yang‐Dong; Jiao, Yong‐Chang; Luo, Chuan‐wei; Zhang, Chi
Abstract: A low profile circularly polarized (CP) antenna with reconfigurable polarization is designed and presented, which can radiate omnidirectional patterns that can be switched between left‐hand circularly polarized (LHCP) and right‐hand circularly polarized (RHCP). A pair of arc‐shaped complementary dipoles is acted as reconfigurable elements by bridging four pin diodes at the dipole arced arms. A meander phase shift line is employed to connected the arc dipole arms and plate cavity to adjust the phase relationship of two sources. The proposed antenna exhibits the omnidirectional radiation pattern by combining six identical elements placed in a circular array configuration. 24 p‐i‐n diodes are exploited to six elements, by manipulating the dc bias voltage across the diodes, the polarization state of the antenna can be switched. The patterns of the antenna are similar to that of a dipole, but its size is only about Φ0.87 × 0.029λ0 at 5.8 GHz. The overlapped bandwidth of measured 3‐dB axial ratio (AR) and 10‐dB return loss is 5.724‐5.87 and 5.738‐5.91 GHz for two polarization states, which are right on the target of ISM band. It can be well adapted to medical diagnosis systems.